Akidah Based Teaching Methods (Analytical, Creative, Innovative, Demonstrative, Active, Humanist) In Elementary Schools: A Literature Review - Pungki Indarto; Gatot Jariono; Rahma Tulloh; Haris Nugroho; Andi Ihsan; Uzizatun Maslikah (UNIB Press, 2023)
The purpose of this study is to find out the initial reference and see other research perspectives as a basis for developing appropriate teaching methods in physical education. This research method uses a literature review using the google scholar search database, eric journal, and Springer. id with keywords analysis methods, creative, innovative, demonstrative, active, humanist in physical education. The articles analyzed are published from 2016 to 2021 using the following specific criteria: indexed by Scopus Q1, Q2, Q3, and Q4. Then national articles indexed sinta 1, sinta 2, sinta 3, and sinta 4. The descriptive method with population, sample, and subject is learners of primary school level. The results of this study can be concluded that the teaching method of AKIDAH-based physical education (Analysis, Creative, Innovative, Demonstrative, Active, and Humanist) is a way of teaching with an approach that is relevant to the development of the times. Choosing a learning method must pay attention to the development and growth of learners, and pay attention to humanist principles with indicators of concern. Analysis of teaching needs requires accuracy, accuracy, suitability (analysis), teaching attracts students (creativity), requires breakthroughs / new things because of the development of science and technology/era (innovative), teachers must be able to become models (demonstrative), how students become (active) in teaching and learning activities of physical education, teaching must humanize humans (humanist) pay attention to the growth and development of students.